IMPLEMENTASI PROGRAM BANTUAN PEMERINTAH ASURANSI NELAYAN BPAN DI KECAMATAN TANGGETADA KABUPATEN KOLAKA - Yudi Agusman; Lode Asrun; Puji Prio Utomo (Journal Publicuho, 2021)
AbstractThe purpose of this study is to analyze the implementation of the Fisherman Insurance Government Program in Tanggetada District, Kolaka Regency. This study uses a qualitative descriptive type of research that provides an overview of all the problems regarding the implementation of the Fisherman Insurance Government Assistance (BPAN) program in Tanggetada District, Kolaka Regency. The results, discussion and conclusions of this study indicate that there are four critical factors that affect the success of the implementation process. The first is communication, where the socialization of BPAN has not gone well, because information about the BPAN program has not been distributed properly to all fishermen in Tanggetada sub-district. Second, natural resources, where there is no socialization budget incentive for employees or extension workers. The third disposition, where the implementation of the Fisherman Insurance Government Assistance program, from the service is not committed because they have not felt the benefits as promised to provide welfare for themselves and their families, there is no democratic nature of the implementer because there are still fishermen who do not get a fisherman insurance card. The fourth is the bureaucratic structure, where the Fisherman Insurance Government Assistance program has SOPso that the implementation has a reference, namely the service is expected to be able to cooperate in the issuance process and the fishermen's insurance claim process.Keywords: Fisherman Insurance; Government Assistance; Implementation  AbstrakTujuan penelitian ini adalah menganalisis Implementasi Program Pemerintah Asuransi Nelayan di Kecamatan Tanggetada Kabupaten Kolaka. Penelitian ini menggunakan jenis penelitian deskriptif kualitatif yaitu memberikan gambaran seluruh permasalahannya tentang implementasi program Bantuan Pemerintah Asuransi Nelayan (BPAN) di Kecamatan Tanggetada Kabupaten Kolaka. Hasil penelitian, pembahasan dan kesimpulan dari penelitian ini menunjukan bahwa terdapat empat critical factors yang mempengaruhi keberhasilan proses implementasi. Pertama komunikasi, dimana dalam sosialisasi BPAN belum berjalan dengan baik, karena informasi tentang program BPAN belum tersalurkan dengan baik kepada seluruh nelayan di kecamatan tanggetada. Kedua sumber daya alam, dimana dalam insentif anggaran sosialisasi yang dilakukan oleh pegawai maupun penyuluh tidak ada. Ketiga disposisi, dimana pelaksanaa program Bantuan Pemerintah Asuransi Nelayan, dari dinas tidak bersikap komitmen karena belum merasakan manfaat seperti yang dijanjikan memberikan kesejahtraan bagi dirinya dan keluarganya, tidak adanya sifat demokratis dari pelaksana karena masih ada nelayan yang tidak mendapatkan kartu asuransi nelayan. Keempat struktur birokrasi, dimana program Bantuan Pemerintah Asuransi Nelayan memiliki SOP agar pelaksanaannya memiliki acuan, yaitu dinas diharpakan dapat menjalin kerjasama dalmam proses penerbitan dan proses klaim asuransi nelayan.    Kata Kunci:   Asuransi Nelayan; Bantuan Pemerintah; Implementasi